Kualitas Pelayanan Reception Di Hotel Danau Toba International Medan - Dameria Girsang; Albert Christoper Nababan (Jurnal Ilmiah Akomodasi Agung, 2021)
In providing good service to guests, Reception plays an important role in a hotel to improve the quality of service to guests at the Danau Toba International Hotel, Medan that has not been carried out properly, especially when guests are at the hotel, check-in and check-out, one of them is the lack of service quality in attention and care for guests, resulting in guests feeling unappreciated. The data were obtained by conducting direct observations in the field, namely the Danau Toba International Hotel, Medan with the library research method and field research through direct interviews with front office staff. In this case, the population and samples in the study are the front office staff, Reception staff and guests who visit Danau Toba International Hotel, Medan. The research was carried out directly at the Front Office at the Danau Toba International Hotel, Medan where the causes of reception service quality problems were found in giving good care and attention to guests, resulting in guests feeling dissatisfied, and not being appreciated in providing good service quality to guests. .